Measuring cognition levels in collaborative processes for software engineering code inspections - McMeekin, D.; Von Konsky, B.; Chang, Elizabeth; Cooper, David (Institute of Electrical and Electronics Engineers (IEEE), 2008)
This paper demonstrates that different software code inspection techniques have the potential to improve developer understanding of code being inspected to varying extents. This suggests that some code inspection techniques may be superior to others with respect to improving the efficacy of future inspections, harnessing collective wisdom, and extending team knowledge and networked intelligence. In particular, this paper reports results from a study of novice developers' cognitive development during a software inspection training exercise. We found that developers who performed a code inspection prior to modification tended to operate at higher cognitive levels beginning very early in the modification exercise. Those who had not performed an inspection tended to operate at lower cognitive levels for longer periods of time. Results highlight the importance of code inspections in increasing developers' understanding of a software system. We believe collaboration between academia and industry in studies such as these would benefit the three major stakeholders: academia, industry and graduates.